Aluminium barium phosphate glass laser emitting at λ = 1.54 µm - Dzyubenko, M.I.; Konradiy, V.A.; Maslov, V.V.; Nikolaev, Yu.P.; Shevchenko, V.V. (Functional Materials, 2008)
A series of samples with various chromium ion concentrations as sensitizing additive have been prepared and studied with respect to manufacturing of active laser elements made of erbium-activated phosphate glass. The spectral, luminescence, and laser characteristics were measured. It has been shown that the synthesides glasses provide high enough laser efficiency attaining about 1.3% in the free-running mode.